Cultura, poder e meio ambiente: sociologia dos trânsitos identitários de uma comunidade rural - Oliveira, Priscila Silveira de (2020)
This thesis sought to understand representations of the rural and meanings attributed to the community life of the residents of a neighborhood in the city of Botucatu called Demétria, which arose from a pioneer experience in the development of biodynamic agriculture in Brazil. Currently, the role of biodynamic agriculture in this context is very small, with only two farmers linked to the biodynamic movement. However, the neighborhood remains with a strong identity linked to Waldorf pedagogy due to the presence of the Aitiara school and also to the principles of Anthroposophy. Our hypothesis was the existence of different social uses of the rural as a category of thought as well as different social uses regarding the identifications around Waldorf pedagogy and Anthroposophy that are linked to class, ethnic and racial differences. Interviews were conducted with residents using a semi-structured questionnaire. From the meanings attributed by the residents of the neighborhood, it was possible to understand a community that recognizes itself from the notion of socio-environmental rural and that emerges linked to a Brazilian social phenomenon at first urban, namely, the logic of condominium in which the closed residential condominium is elevated to a hegemonic way of life paradigm in the Brazilian national imaginary. Thus, our work presents different moments historically in the formation of the neighborhood, namely: the construction of Estância Demétria and the construction of the Waldorf school “Aitiara” and coming from first fixed and intermittent residents, linked to the process of building an identity associated with anthroposophy and building a community; a second moment, when agricultural production ceases to have a preponderant role in territorial organization, the arrival of new residents and the growth of the neighborhood present new identifications, the rural as landscape, nature and idyllic space, and the Aitiara school become the nuclei of these discursive practices. It is the period that establishes and expands frontiers between Demétria and the city of Botucatu. A third moment, which extends to the present day in which, the great growth of the neighborhood and the number of residents, presents Demetria very heterogeneous, the “demetrian” identity and a sense of community become more and more associated with condominium logic. At that moment, sustainable consumption and the relations with this space as a “commodity”, promote the growing real estate speculation in the neighborhood and reveal influences of the neoliberal ideology regarding the identifications to the rural and socio-environmental issue. In this regard, we seek to analyze the transformations, challenges and potentialities for identity issues in late capitalism, notably regarding the potentialities of the emergence of environmental sustainability as a new identity paradigm in the face of the emergence of the neoliberal subject.